Ferroptosis-Related Gene Signature Predicts Glioma Cell Death and Glioma Patient Progression - Liu, Han-jie; Hu, Hui-min; Li, Guan-zhang; Zhang, Ying; Wu, Fan; Liu, Xiu; Wang, Kuan-yu; Zhang, Chuan-bao; Jiang, Tao (Frontiers in Cell and Developmental Biology, 2020)
Glioma is a fatal brain tumor characterized by rapid proliferation and treatment resistance. Ferroptosis is a newly discovered programmed cell death and plays a crucial role in the occurrence and progression of tumors. In this study, we identified ferroptosis specific markers to reveal the relationship between ferroptosis-related genes and glioma by analyzing whole transcriptome data from Chinese Glioma Genome Atlas, The Cancer Genome Atlas dataset, GSE16011 dataset, and the Repository of Molecular Brain Neoplasia Data dataset. Nineteen ferroptosis-related genes with clinical and pathological features of glioma were identified as highly correlated. Functional assays in glioma cell lines indicated the association of ferroptosis with temozolomide resistance, autophagy, and glioma cell migration. Therefore, the identified ferroptosis-related genes were significantly correlated with glioma progression.